Effect of additives on the melt rheology and thermal degradation of poly[(R)‐3‐hydroxybutyric acid]. Issue 15 (30th December 2014) - Arza, Carlos R.; Jannasch, Patric; Johansson, Peter; Magnusson, Per; Werker, Alan; Maurer, Frans H. J.
ABSTRACT Thermal degradation of poly[(R)−3‐hydroxybutyric acid] (PHB) during melt mixing results in random chain scission that produces shorter polymer chains containing crotonic and carboxyl end groups. One way of preventing this serious reduction of molar mass is to add agents that react with at least two of the newly generated end groups. Different types of commercially available additives known to react with carboxyl group, namely bis(3, 4‐epoxycyclohexylmethyl) adipate (BECMA), 2, 2'‐bis(2‐oxazoline) (BOX), trimethylolpropane tris(2‐methyl‐1‐aziridinepropionate) (PETAP), triphenyl phosphate (TPP), tris(nonylphenyl) phosphate (TNPP), polycarbodiimide (PCDI), and poly(methyl metharylate‐co‐glycidyl methacrylate) (GMA.MMA) were mixed with PHB by cocasting from solution in chloroform. Dynamic rheology as well as measurements of molar masses before and after dynamic analysis was used to evaluate the effect of the additives on the melt stability of PHB. Measurements of the dynamic shear modulus and the molar mass of molten PHB with the additives PCDI and GMA.MMA showed a minor improvement on the thermal stability. Furthermore, TPP and TNPP did not affect the thermal stability of PHB, whereas the presence of BECMA, BOX, and PETAP gave a strong decrease of the dynamic modulus compared with neat PHB. © 2014 The Authors Journal of Applied Polymer Science Published by Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41836.